SL4, a chalcone‐based compound, induces apoptosis in human cancer cells by activation of the ROS/MAPK signalling pathway. (26th October 2015) - Wang, L.‐H.; Li, H.‐H.; Li, M.; Wang, S.; Jiang, X.‐R.; Li, Y.; Ping, G.‐F.; Cao, Q.; Liu, X.; Fang, W.‐H.; Chen, G.‐L.; Yang, J.‐Y.; et al.
Abstract: Objectives: SL4, a chalcone‐based compound, exhibits clearly inhibitory effects on HIF‐1 and has been shown to effectively suppress tumour invasion and angiogenesis in vitro and in vivo . Here, studies were conducted to determine SL4's anti‐apoptotic effects and its underlying mechanisms, in human cancer cells. Materials and methods: Cytotoxicity, apoptotic induction and its involved mechanisms of SL4 were investigated using normal cells, cancer cells and mouse xenograft models. The role of reactive oxygen species (ROS) and mitogen‐activated protein kinase (MAPK) signalling in SL4‐induced apoptosis was explored by manipulating specific scavenger or signalling inhibitors, in cultured cells. Results: SL4 significantly inhibited cell population growth of human cancer cell lines but exhibited lower cytotoxicity against normal cells. In addition, SL4 effectively induced apoptosis of Hep3B and MDA‐MB‐435 cells by activating procaspase‐8, ‐9 and ‐3, and down‐regulating expression levels of XIAP, but did not affect HIF‐1 apoptosis‐related targets, Survivin and Bcl‐XL . Further study showed that SL4 also reduced mitochondrial membrane potential and promoted generation of ROS. ROS generation and apoptotic induction by SL4 were blocked by NAC, a scavenger of ROS, suggesting SL4‐induced apoptosis via ROS accumulation. We also found that MAPKs, JNK and p38, but not ERK1/2, to be critical mediators in SL4‐induced apoptosis. SP600125 and SB203580, specific inhibitors of JNK kinase and p38 kinase, significantly retarded apoptosis induced by SL4. Moreover, anti‐oxidant NAC blocked activation of JNK and p38 induced by SL4, indicating that ROS may act as upstream signalling of JNK and p38 activation. It is noteworthy that animal studies revealed dramatic reduction (49%) in tumour volume after 11 days SL4 treatment. Conclusions: These data demonstrate that SL4 induced apoptosis in human cancer cells through activation of the ROS/MAPK signalling pathway, suggesting that it may be a novel lead compound, as a cancer drug candidate, with polypharmacological characteristics.